Inherent Features and the Root Process of the Screen Text as the Audio- Visual Simulation of Reality - O. L. Maksimenko; Y. A. Evgrafova (Концепт: философия, религия, культура, 2020)
The article touches upon the issue of functions and features of screen text. Being generally a form of text, being expressed, semiotically separated and structured, screen text follows the same lines of general and linguistic semiotics as average texts. However, it is a multicomponent system. Among its characteristics it is possible to distinguish heterogeneity and polysemy that render it the audio-visual reflection, or rather simulation of reality. This article is a case study of a specific type of texts which are called polycode-polymodal. Logical and descriptive methods as well as observation, generalization, interpretation are the foundation of analyzing heterogeneous screen texts such as film texts, television texts and video texts of the Internet. On the exempl of various texts of visual arts and media the root process of text as specific mechanisms of framing the language used and, thus, the images and the meaning. Fundamental characteristics of the screen text – openness, psychological and aesthetic stimuli – are illustrated in descriptions of the root process. The paper contributes to revealing that the screen text obtains such features as heterogeneity, hierarchy, and polysemy, deriving from the root process of the screen text. Heterogeneity of the screen text directly influences its polysemy and makes screen text an open system. Polysemy, experience and likelihood, then, belong to the psychological stimulus; affectability, suggestive potential, suggestive infusion belong to the aesthetic stimulus. In turn, psychological and aesthetic stimuli are manifested in the screen text. Study of the root process and peculiarities of the screen text helps describe the schemes of constructing the secondary reality and simulacra on the screen, and also helps list the means of manipulation with the consciousness of the viewer in more detail.